2018
DOI: 10.1037/cou0000304
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of transmasculine spectrum people who report nonsuicidal self-injury: A qualitative investigation.

Abstract: Transgender populations experience mental and physical health disparities compared to nontransgender populations, including nonsuicidal self-injury (NSSI). Guided by the minority stress theory and Nock's model of NSSI, this study explored perspectives of transmasculine spectrum people (i.e., people with a gender identity that is man, male, transgender man, genderqueer, or nonbinary and who were assigned female at birth) who engage in NSSI. Qualitative interviews were conducted with transmasculine spectrum peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 59 publications
(82 reference statements)
2
11
0
Order By: Relevance
“…We set out to examine associations between stigma and NSSI in the last year, and tested resilience factors and identity-related variables that emerged from formative, qualitative research (Jackman et al, 2018). The qualitative study revealed that among transmasculine spectrum people who reported self-injury, in addition to stigma at various levels, stressors related to transgender identity development were also important for understanding vulnerability and resilience to NSSI.…”
Section: Introductionmentioning
confidence: 99%
“…We set out to examine associations between stigma and NSSI in the last year, and tested resilience factors and identity-related variables that emerged from formative, qualitative research (Jackman et al, 2018). The qualitative study revealed that among transmasculine spectrum people who reported self-injury, in addition to stigma at various levels, stressors related to transgender identity development were also important for understanding vulnerability and resilience to NSSI.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is argued that being in a disempowered position can make it harder to have control or to communicate, which can consequently lead to NSSI. This finding has significant implications for understanding NSSI within marginalized populations, such as those within the LGBTQ+ community, who are at higher risk of engaging in NSSI (Jackman et␣al., 2018; Taylor, Dhingra, Dickson, & McDermott, 2018). Future research would be beneficial in exploring specific links between the kinds of challenging interpersonal experiences and unmet interpersonal needs, and the way in which NSSI is utilized as a substitutive coping strategy, both in a broad sense but also within certain more affected populations.…”
Section: Discussionmentioning
confidence: 99%
“…And then nobody is listening to me, and so I just started cutting. Power, Brown, and Usher (2013;p.199) This was an experience for some LGBTQ+ participants who saw self-injury as an alternative when faced with a lack of community or support (Jackman, Edgar, Ling, Honig, & Bockting, 2018). The participants convey a sense of not perceiving themselves to matter in the minds of others, or to have given up on them.…”
Section: A Disempowered Statementioning
confidence: 99%
See 2 more Smart Citations